The Effect of Financial Inclusion, Financial Planning, and Saving Interests on the Performance of MSME Actors in Sidoarjo Regency: Pengaruh Inklusi Keuangan, Perencanaan Keuangan, dan Minat Nabung Terhadap Kinerja Pelaku UMKM di Kabupaten Sidoarjo - Zannah, Harum Umi Nur; Setiyono, Wisnu Panggah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze and examine the effect of Financial Inclusion, Financial Planning, and Savings Interests on the Performance of MSME Actors in Krembung District.This study uses quantitative methods and the object of this research is the population and random samples (purposive sampling), namely SMEs in the Krembung sub-district. The data used in this study is primary data obtained from filling out questionnaires carried out by 25 respondents. people who are the sample in the study. The data analysis technique uses data quality checking, classical assumption test and multiple linear regression analysis using the SPSS application.Based on the results of the study, it can be concluded that financial inclusion (X1) has a significant effect on the performance of MSME actors in the Krembung sub-district which is engaged in services, food, craft, financial planning (X2) has a significant effect on the performance of MSME actors in the Krembung sub-district which are engaged in services, food, craft, saving interest (X3) have a significant effect on the performance of MSME actors in the Krembung sub-district which are engaged in services, food, craft.